2009
DOI: 10.1161/strokeaha.108.527978
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Recent Sports Activity, Sports Activity in Young Adulthood, and Stroke

Abstract: Background and Purpose-Leisure-time physical activity protects from stroke. It is insufficiently established whether early lifetime physical activity is independently protective and whether some etiologic stroke subgroups particularly benefit from physical activity. We tested the hypothesis that both recent and early-adulthood sports activities are associated with reduced odds of stroke and analyzed their effects in stroke subtypes. Methods-We performed a case-control study of 370 patients with acute stroke or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…We studied 370 consecutive patients admitted to the Neurology Department of the University of Heidelberg for ischemic or hemorrhagic stroke or transient ischemic attack (TIA) and 370 control subjects randomly selected from the general population between November 2001 and April 2003 [9,10]. Patients who were >80 years (>75 years after the first 6 months of the study), resided outside the study area (city of Heidelberg and the neighboring county) or were unable to give informed consent were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied 370 consecutive patients admitted to the Neurology Department of the University of Heidelberg for ischemic or hemorrhagic stroke or transient ischemic attack (TIA) and 370 control subjects randomly selected from the general population between November 2001 and April 2003 [9,10]. Patients who were >80 years (>75 years after the first 6 months of the study), resided outside the study area (city of Heidelberg and the neighboring county) or were unable to give informed consent were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Control subjects were randomly selected from the general population and matched to patients one-to-one for age (±2 years), sex and area of residence [9,10]. Within 1 week after a patient was included, the first matching subject identified from a 2% random sample of the study population was contacted by mail and thereafter by phone.…”
Section: Methodsmentioning
confidence: 99%
“…These diseases are commonly referred to as, 'sedentariness'. As such, lifelong physical activity, or beginning physical activity at any stage of life, results in significant cardiovascular health benefits [14]. Modern lifestyles, have forced people to be less active, as much time is spent watching television, searching the internet, electronic game playing and reading.…”
Section: The Benefits Of Exercise To Healthmentioning
confidence: 99%
“…Therefore, the results suggested that staying active to old age may be beneficial against ischemic stroke. A German case-control study of 740 subjects similarly observed a significant reduction in stroke risk among older adults who remained physically active but not those active only during their young adulthood [21], while results from another case-control study with 127 patients and 301 subjects conducted in Demark indicated a potential protective effect of most recent physical activities against ischemic stroke [11]. The protective effect of regular physical activity is biologically plausible.…”
Section: Discussionmentioning
confidence: 99%